Characterizing renewable energy compound events across Europe using a logistic regression‐based approach. (13th September 2022) - Otero, Noelia; Martius, Olivia; Allen, Sam; Bloomfield, Hannah; Schaefli, Bettina
Abstract: The transition towards decarbonized power systems requires accounting for the impacts of the climate variability and climate change on renewable energy sources. With the growing share of wind and solar power in the European power system and their strong weather dependence, balancing the energy demand and supply becomes a great challenge. We characterize energy compound events, defined as periods of simultaneous low renewable production of wind and solar power, and high electricity demand. Using a logistic regression approach, we examine the influence of meteorological and atmospheric drivers on energy compound events. Moreover, we assess the spatial coherence of energy compound events that pose a major challenge within an interconnected power grid, as they can affect multiple countries simultaneously. On average, European countries are exposed to winter energy compound events more than twice per year. The combination of extremely low temperatures and low wind speeds is associated with a higher probability of occurrence of energy compound events. Furthermore, we show that blocked weather regimes have a major influence on energy compound events. In particular, Greenland and European blocking lead to widespread energy compound events that affect multiple countries at the same time. Our results highlight the relevance of weather regimes resulting in synchronous spatial energy compound events, which might pose a greater risk within a potential fully interconnected European grid. Abstract : European countries are exposed to energy compound events, during which it might be challenging to achieve a balanced electricity transmission system, due to simultaneous episodes of high electricity demand (left) and low renewable energy production (right). Synchronous energy compound events can affect multiple countries simultaneously (black starts). In particular, the European power system is vulnerable to blocked weather regimes, which have a large influence on the renewable production and electricity demand in Europe.